Ética en la investigación en gestión: relevancia, principios y lineamientos para su aplicación - Pasco Dalla Porta, Mario (2016)
In recent decades, many universities and other research centers have developed codes and created committees with the purpose of incorporating ethical parameters in the generation of scientific knowledge. Greater progress in health disciplines and certain social sciences has been more remarkable; however, progress has been slower in management sciences. In this context, this paper intends to review theoretical-methodological literature on management to assess the relevance of ethics in knowledge generation and to highlight related ethical principles and institutional practices. Then, a sample of research documents on management is tested, with the purpose of demonstrating the limited discussion of ethical issues, either at a general level (research published in top academic journals in the discipline) or at a specific level (research produced at the management program at the Pontificia Universidad Católica del Perú). Accordingly, the paper posits guidelines aimed at including ethical considerations in the generation of disciplinary knowledge. Finally, a brief discussion on the main topics addressed is provided.